RESTORATIVE JUSTICE DITINJAU DARI PENEMUAN HUKUM SEBAGAI ALTERNATIF PENYELESAIAN TINDAK PIDANA - Fakhrul Ardiyan; Irwan Triadi (JOURNAL OF LAW AND NATION, 2025)
The principle of law enforcement according to the 1945 Constitution (UUD) Republic of Indonesia means that Indonesia is a country based on the rule of law with an affirmation of people's sovereignty and government based on a constitutional system, and that citizens have equal standing before the law. Law enforcement is a reflection of the principle of the supremacy of law, which states that legal actions must be based on laws that do not conflict with applicable laws and regulations, as well as equality before the law, which states that everyone has the same status before the law and has the right to protection. The settlement of non-criminal cases through a restorative justice approach shows progress or a positive development in law enforcement. The concept of a restorative justice approach is one that tends to create justice and balance for perpetrators of criminal acts or restitution and compensation for victims. Indonesia is a country that adheres to a civil law system, which prioritizes positive law in the process of enforcing justice. The enforcement of justice is carried out by judges who make decisions on offenders based on applicable laws and regulations. However, the presence of restorative justice has brought about a shift in the application of conventional criminal proceedings in particular. If restorative justice is implemented in a manner that is inconsistent with the principles of positivism or legality, then this approach becomes ambiguous in its application in Indonesia. The rules governing the restorative justice approach represent a void in criminal law regulations. It should be noted that the emergence and implementation of the restorative justice approach is a matter of legal discovery or interpretation that has only recently come to light.